2008
DOI: 10.1007/s10886-008-9455-x
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Enhancement and Differential Gene Expression in Rice under Low Nitrogen Treatment

Abstract: The allelopathy-competition separation (ACS) based approach was used to explore the biointerference relationship between rice accessions and barnyardgrass exposed to different nitrogen (N) supplies in hydroponics. Rice accession PI312777 exhibited high allelopathic potential to suppress the growth of accompanying weeds, especially when the culture solution had low N content. The non-allelopathic rice Lemont showed an opposite result. Additionally, subtractive hybridization suppression (SSH) was used to constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 33 publications
4
46
0
Order By: Relevance
“…The present result suggested that the SA-mediated cascade reaction in rice to defend against barnyardgrass attack might be similar to the responses to nutrient deficiency through the regulation of carbon-nutrient balance (Bryant et al 1987). This in turn results in the accumulation of phenolics and more phenolic allelochemicals being released into external environment (culture solution) from the roots to depress the target weed growth including the inhibition of protective enzyme activity and root uptake ability, which was consistent with the previous studies (Lin et al 2000;Bi et al 2007;Xiong et al 2007b;Shen et al 2008;Song et al 2008). This raises the question as to why the autotoxicity does not occur during this process.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present result suggested that the SA-mediated cascade reaction in rice to defend against barnyardgrass attack might be similar to the responses to nutrient deficiency through the regulation of carbon-nutrient balance (Bryant et al 1987). This in turn results in the accumulation of phenolics and more phenolic allelochemicals being released into external environment (culture solution) from the roots to depress the target weed growth including the inhibition of protective enzyme activity and root uptake ability, which was consistent with the previous studies (Lin et al 2000;Bi et al 2007;Xiong et al 2007b;Shen et al 2008;Song et al 2008). This raises the question as to why the autotoxicity does not occur during this process.…”
Section: Discussionsupporting
confidence: 86%
“…After 7 days of recovery in the Hoagland nutrient solution, 30 rice seedlings and 10 weed seedlings were transplanted into a Styrofoam plate to form a hydroponic rice-weed mixture with the barnyardgrass seedlings in the center surrounded by the rice seedlings. This setting could induce rice allelopathy (Belz and Hurle 2004;Kim et al 2005;Xiong et al 2005;Song et al 2008). Three SA treatments were set at the concentrations of 0.1, 0.2, and 0.3 mM.…”
Section: Preparation For Plant Materialsmentioning
confidence: 99%
“…A number of recent studies have reported cellular and molecular processes involved in the production of allelochemicals and the response of target plants (Baerson et al, 2005;Dayan, 2006;Ding et al, 2007;Golisz et al, 2008;Song et al, 2008). During the molecular oxygen reduction process, intermediate molecules known as Reactive Oxygen Species (ROS) [e.g., superoxide (O .− 2 ), hydrogen peroxide (H 2 O 2 ) and hydroxyl radical (OH . )]…”
Section: Releasing Allelopathic Compounds Into the Environmentmentioning
confidence: 99%
“…However, current knowledge on allelopathic QTL remains incomplete (Belz, 2007). Song et al (2008) demonstrated the intensification of allelochemical biosynthesis in rice grown under stress nutrition (i.e., low levels of nitrogen). This experiment revealed the overexpression of genes that encode for PAL (phenylalanine ammonia-lyase), O-methyltransferase, triosephosphate isomerase and P450 -all related to the synthesis of phenolic compounds and detoxification.…”
Section: Genetic Improvement Of Allelopathic Activity In Cropsmentioning
confidence: 99%
“…A few recent studies include those on: juglone effects on root plasma membrane H + ATPase activity and root water uptake (Hejl and Koster 2004); the use of polydimethylsiloxane materials to quantify levels of the photosynthesis inhibitor sorgoleone in the rhizosphere of sorghum plants (Weidenhamer 2005); the critical evaluation of the contribution of (±)-catechin to invasion success of spotted knapweed (Blair et al 2005(Blair et al , 2006; degradation of soluble phenolics by ectomycorrhizal fungi, thus controlling species interactions in black spruce stands (Zeng and Mallik 2006); selective phytotoxicity of L-DOPA because of differential polyphenol oxidase activity in barnyard grass and lettuce, thus mediating reactive oxygen species and/or free radical species (Hachinohe and Matsumoto 2007); and differential gene expression in rice under low nitrogen due to stronger activation of genes that function in synthesis of allelochemicals (Song et al 2008).the term allelopathy. In his experiments, he used the odor of apple peels, mainly comprised of ethylene, as a model system to explore effects of volatile emissions on the development of a range of plant species.…”
Section: Introductionmentioning
confidence: 99%